5-HT7R enhances neuroimmune resilience and alleviates meningitis by promoting CCR5 ubiquitination - Zhenfang Gao; Yang Gao; Yuxiang Li; Jie Zhou; Ge Li; Shun Xie; Ruiyan Jia; Lanying Wang; Ziying Jiang; Meng Liang; Chunxiao Du; Yaqiong Chen; et al. (Journal of Advanced Research)
Introduction: Excessive immune activation induces tissue damage during infection. Compared to external strategies to reconstruct immune homeostasis, host balancing ways remain largely unclear. Objectives: Here we found a neuroimmune way that prevents infection-induced tissue damage. Methods: By FACS and histopathology analysis of brain Streptococcus pneumonia meningitis infection model and behavioral testing. Western blot, co-immunoprecipitation, and ubiquitination analyze the Fluoxetine initiate 5-HT7R-STUB1-CCR5 K48-linked ubiquitination degradation. Results: Fluoxetine, a selective serotonin reuptake inhibitor, or the agonist of serotonin receptor 5-HT7R, protects mice from meningitis by inhibiting CCR5-mediated excessive immune response and tissue damage. Mechanistically, the Fluoxetine-5-HT7R axis induces proteasome-dependent degradation of CCR5 via mTOR signaling, and then recruits STUB1, an E3 ubiquitin ligase, to initiate K48-linked polyubiquitination of CCR5 at K138 and K322, promotes its proteasomal degradation. STUB1 deficiency blocks 5-HT7R-mediated CCR5 degradation. Conclusion: Our results reveal a neuroimmune pathway that balances anti-infection immunity via happiness neurotransmitter receptor and suggest the 5-HT7R-CCR5 axis as a potential target to promote neuroimmune resilience.